Is conduction system pacing improving cardiac performance in patients with right bundle branch block and heart failure? - Jing-Jing, Jia; Xi-Xia, Sun; Tian-Zhu, Li; Xin, Wang; Xiao-Lei, Yang; Xin-Jing, Ai; Yun-Long, Xia; Ying-Xue, Dong (Frontiers in Physiology, 2025)
ObjectiveThe aim of this study was to evaluate the feasibility and safety of conduction system pacing (CSP) in patients with right bundle branch block (RBBB) and heart failure (HF).MethodsThis retrospective study included all the patients with HF and a ventricular pacing frequency of more than 40% who underwent CSP between 2018 and 2023, with all enrolled patients presenting RBBB prior to the procedure. Clinical data, including echocardiographic and electrocardiographic findings, were collected before and after the procedure, with a minimum follow-up duration of 2 years.ResultsCSP was successfully performed in 78 patients (78/88, 88.63%), comprising 13 patients (13/78, 16.67%) with His-bundle pacing (HBP) and 65 patients (65/78, 83.33%) with left bundle branch pacing (LBBP). Significant improvements were observed in QRS duration (148.06 ± 17.91 ms vs. 121.87 ± 14.47 ms, p < 0.001), left ventricular ejection fraction (LVEF) (43.79% ± 11.71% vs. 46.94% ± 10.06%, p = 0.020), left ventricular end-diastolic diameter (LVEDD) (54.15 ± 7.67 mm vs. 52.71 ± 7.67 mm, = 0.016), and the New York Heart Association (NYHA) functional class (2.97 ± 0.68 vs. 1.63 ± 1.08, p = 0.001). No significant change was noted in the left atrial diameter (LAD) (44.72 ± 8.07 mm vs. 43.86 ± 8.42 mm, p = 0.114). Subgroup analysis revealed that a marked LVEF improvement was observed in patients with baseline LVEF ≤35% (30.05% ± 2.76% vs. 41.42% ± 11.61%, p = 0.001). Logistic regression analysis revealed that LVEF (OR = 0.112, 95% CI: 0.011–0.839, and p = 0.001) and ΔQRS (OR = 1.449, 95% CI: 1.292–2.445, and p = 0.021) were independent predictors of echocardiographic response.ConclusionCSP is safe and effective for patients with RBBB and HF, with particularly notable improvements in cardiac performance among those with severely reduced LVEF.